PRODUCING GOOD STORIES IN ENGLISH AS A FOREIGN LANGUAGE: ANALYSIS OF THE KURDISH EFL LEARNERS’ ORAL “FROG STORY” NARRATIVES - EBRAHIM, HALLAT RAJAB (Journal of Duhok University, 2020)
By focusing on the structural elements particularly the evaluative devices by (Labov & Waletzky, 1967) and (Peterson & McCabe, 1991), this study examined how the Kurdish participants’ narrative discourse deviate from the target language discourse, and how this deviation is explained in line with the cultural discourse strategies in both types of discourse (Kurdish and English). This study analyzed the frog narratives told by the EFL Kurdish participants (in Kurdish and English) and the American speakers with special attention on the narrative length, narrative structure and evaluative devices. The findings from the T-test and MANOVA statistics revealed cross-cultural patterns of differences between the narratives told by the Kurdish and the American speakers. Generally, the narratives told by the American participants were longer than those told by the Kurdish participants in both Kurdish and English. The American speakers elicited narratives with frequent evaluation. Conversely, the Kurdish participants constructed narratives with higher number of durative (descriptive) clauses, orientation and repetition.